2016
DOI: 10.1536/ihj.15-271
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Accelerated Thrombolysis May Be an Effective and Safe Treatment Modality for Intermediate Risk/Submassive Pulmonary Embolism

Abstract: SummaryPulmonary embolism (PE) is a potentially life-threatening condition and the fact that 90% of PE originate from lower limb veins highlights the significance of early detection and treatment of deep vein thrombosis.1) Massive/high risk PE involving circulatory collapse or systemic arterial hypotension is associated with an early mortality rate of approximately 50%, in part from right ventricular (RV) failure.2) Intermediate risk/submassive PE, on the other hand, is defined as PE-related RV dysfunction, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…The use of new devices for fragmentation and/or aspiration of the thrombi can improve these results. The use of ultrasound through a 5.4 Fr catheter with infusion of fibrinolytic leads to rapid lysis of the thrombi located in the pulmonary artery[40,50,51]. Seattle II, a prospective study of 150 patients diagnosed with massive or submassive PE using EKO-sonic and a low dose of r-TPA through CDT, reduced the RV/LV ratio measured with CT by 25% in 48 h, showed a 30% improvement of the systolic pressure and another 30% in the pulmonary artery obstruction[41].…”
Section: Results Of Endovascular Techniques For the Treatment Of Pementioning
confidence: 99%
“…The use of new devices for fragmentation and/or aspiration of the thrombi can improve these results. The use of ultrasound through a 5.4 Fr catheter with infusion of fibrinolytic leads to rapid lysis of the thrombi located in the pulmonary artery[40,50,51]. Seattle II, a prospective study of 150 patients diagnosed with massive or submassive PE using EKO-sonic and a low dose of r-TPA through CDT, reduced the RV/LV ratio measured with CT by 25% in 48 h, showed a 30% improvement of the systolic pressure and another 30% in the pulmonary artery obstruction[41].…”
Section: Results Of Endovascular Techniques For the Treatment Of Pementioning
confidence: 99%
“…Thrombolytic and anticoagulation therapy, therapy for heart failure, and implantable cardioverter defibrillator are important after disappearance of the thrombi. Furthermore, ultrasound accelerated thrombolysis 5) or veno-arterial extracorporeal membrane oxygenation 6) can be effective treatments for submassive or massive pulmonary embolism. The present case demonstrates that VT is not always the sole contributor to syncope and death in patients with ARVC, and pulmonary embolism should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,12 CDTs have demonstrated improved RV dysfunction, decreased pulmonary artery pressures, and reduced risks of major bleeds. 1,4,13,14,15,16 The recent development of ultrasound-assisted, low-dose fibrinolysis therapy (USAT), a variation of CDT, has provided another treatment modality for the management of acute submassive PEs (ASMPEs). 17 USAT incorporates ultrasound-generated acoustic energy to facilitate disruption of the PE allowing for improved fibrinolytic penetration.…”
Section: Introductionmentioning
confidence: 99%
“…17 USAT incorporates ultrasound-generated acoustic energy to facilitate disruption of the PE allowing for improved fibrinolytic penetration. 16 Two landmark studies, SEATTLE II and ULTIMA, demonstrated the efficacy and safety of USAT for ASMPEs while maintaining low rates of bleeding complications. 8,9 Another study, OPTALYSE PE, determined the lowest optimal tissue plasminogen activator (tPA) dose and delivery duration using USAT for the treatment of ASMPEs.…”
Section: Introductionmentioning
confidence: 99%